Pubblici uffici e competenze grafiche nell’età carolingia: una relazione biunivoca? Il caso di Lucca - Mastruzzo, Antonino; Unfer Verre, Gaia Elisabetta (Scrineum, 2021)
The authors examine the way in which the paleographic analysis can enrich the historical knowledge of the public administration in a local context of the Carolingian age. In particular, the case of Lucca is examined. In fact, Lucca offers a privileged point of observation due to the extraordinary richness of its surviving documentation. The analysis focuses on only one type of contract: the exchange that involves ecclesiastical institutions. Finally, the possibility of a more in-depth material analysis of the early medieval document is presented, aiming not only at handwriting classification but also at understanding the timing according to which documents were written.